The Role of Authentic Leadership in Project Success: Exploring the Mediating Effect of Trust and the Moderating Influence of Charisma - Ali Shams, Haider; Waheed, Hushsham; Aamir, Adeel Ahmad; Ali Shams, Mohsin; Ahmed, Sana (2025)
The purpose of the study is to determine whether trust mediated the effect of authentic leadership on project success. Additionally, a moderator (leadership charisma) was also evaluated using a moderated mediation approach. To address the primary aims, to measure the project manager's authentic leadership style, trust, charisma, and project achievement in project-based organizations of developing countries a questionnaire-based survey was used. The analyses suggest that increases in levels of authentic leadership enhance trust among team members and eventually contribute massively to project success. The results also show that charisma shows a statistically significant influence on developing trust. Finally, the findings suggest that charisma has a moderating effect on the relationship between authentic leadership dimensions and overall project success. The new method as suggested by Preacher and Hayes “process” was used to study this impact, which would contribute to method advancement in variables testing in the specific context of project management and leadership.